The Proportion of Individuals Likely to Benefit from Customized Optic Nerve Head Structure-Function Mapping - McKendrick, Allison M; Denniss, Jonathan; Wang, Ya Xing; Jonas, Jost B; Turpin, Andrew (Ophthalmology (Rochester, Minn.), 2017)
Interindividual variance in optic nerve head (ONH) position, axial length, and location of the temporal raphe suggest that customizing mapping between visual field locations and ONH sectors for individuals may be clinically useful. Herein we quantify the proportion of the population predicted to have structure-function mappings that markedly deviate from "average," and thus would benefit from customized mapping. Database study and case report. Population database of 2836 eyes from the Beijing Eye Study and a single case report of an individual with primary open-angle glaucoma. Using the morphometric fundus data of the Beijing Eye Study for 2836 eyes and applying a recently developed model based on axial length and ONH position relative to the fovea, we determined for each measurement location in the 24-2 Humphrey (Carl Zeiss Meditec, Dublin, CA) visual field the proportion of eyes for which, in the customized approach as compared with the generalized approach, the mapped ONH sector was shifted into a different sector. We determined the proportion of eyes for which the mapped ONH location was shifted by more than 15°, 30°, or 60°. Mapping correspondence between locations in visual field space to localized sectors on the ONH. The largest interindividual differences in mapping are in the nasal step region, where the same visual field location can map to either the superior or inferior ONH, depending on other anatomic features. For these visual field locations, approximately 12% of eyes showed a mapping opposite to conventional expectations. Anatomically customized mapping shifts the map markedly in approximately 12% of the general population in the nasal step region, where visual field locations can map to the opposite pole of the ONH than conventionally considered. Early glaucomatous damage commonly affects this region; hence, individually matching structure to function may prove clinically useful for the diagnosis and monitoring of progression within individuals.